Effects of Ginkgo biloba Extract on Inflammatory Mediators (SOD, MDA, TNF-α, NF-κBp65, IL-6) in TNBS-Induced Colitis in Rats - Yan-Hong Zhou; Jie-Ping Yu; Yi-Fei Liu; Xiao-Jun Teng; Mei Ming; Peng Lv; Ping An; Shi-Quan Liu; Hong-Gang Yu (Mediators of Inflammation)
Inflammatory mediators play a criticial role in ulcerative colitis immune and inflammatory processes. The aim of the study was to investigate the effects of Ginkgo biloba extract on inflammatory mediators (SOD, MDA, TNF-α, NF-κBp65, IL-6) in TNBS-induced colitis in rats. Colitis in rats was induced by colonic administration with 2,4,6-trinitrobenzene sulfonic acid (TNBS, 150 mg/kg). EGB in doses of (50, 100, 200 mg/kg) was administered for 4 weeks to protect colitis. The results showed that EGB could significantly ameliorate macroscopic and histological damage, evidently elevate the activities of SOD and reduce the contents of MDA, inhibit the protein and mRNA expressions of TNF-α, NF-κBp65, and IL-6 in the colon tissues of experimental colitis in a dose-dependent manner compared with the model group. We concluded that the probable mechanisms of EGB ameliorated inflammatory injury in TNBS-induced colitis in rats by its modulation of inflammatory mediators and antioxidation.